2023
DOI: 10.1063/5.0146162
|View full text |Cite
|
Sign up to set email alerts
|

Gender in human phonation: Fluid–structure interaction and vocal fold morphology

Abstract: This paper aims to examine the effects of variations in the vocal fold (VF) morphological features associated with gender on glottal aerodynamics and tissue deformation. Nine three-dimensional geometries of the VFs in the larynx are created with various VF lengths, thicknesses, and depths to perform a parametric analysis according to gender-related geometrical parameters. The computational model is incorporated in a fluid–structure interaction methodology by adopting the transient Navier–Stokes equations to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…A clinical study has demonstrated the differences in vocal tract geometry between males and females [4]. McCollum et al [5] numerically simulated the airflow in nine channel models with different geometry and gave the vibrations of vocal tracts under the action of airflow, thus indicating the effect of changes in geometry on vocalization. Šidlof [6] has also explored the vocalization process of the human vocal tract through numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical study has demonstrated the differences in vocal tract geometry between males and females [4]. McCollum et al [5] numerically simulated the airflow in nine channel models with different geometry and gave the vibrations of vocal tracts under the action of airflow, thus indicating the effect of changes in geometry on vocalization. Šidlof [6] has also explored the vocalization process of the human vocal tract through numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that the geometries of the channels considered in the literature [5,6] are symmetric, while the numerical results of the flow fields are asymmetric at some specific value ranges of the characteristic parameter Reynolds number (Re). In addition, all the boundary conditions of the given problem are independent of time; however, the numerical results of the flow field are oscillatory and time dependent when Re exceeds a certain Mathematics 2024, 12, 553 2 of 14 critical value (Rec).…”
Section: Introductionmentioning
confidence: 99%